Tinzaparin and enoxaparin given at prophylactic dose for eight days in medical elderly patients with impaired renal function - Mahé, Isabelle; Aghassarian, Manvel; Drouet, Ludovic; dit-Sollier, Claire Bal; Lacut, Karine; Heilmann, Jean-Jacques; Mottier, Dominique; Bergmann, Jean-François (Thrombosis and Haemostasis, 2007)
Low-molecular-weight heparins (LMWHs) accumulate in patients with impaired renal function. As this accumulation depends on heparin chain length and subsequent reticulo-endothelial/renal elimination, LMWHs might have different pharmacodynamic profiles. The primary objective was to examine if any accumulation effect of two LMWHs, enoxaparin and tinzaparin, occurred after repeated administration of a prophylactic dose over eight days in elderly patients (age >75 years) with creatinine clearance between 20 and 50 ml/min and body weight <65Kg. Patients were openly randomized to two groups (enoxaparin 4,000 IU or tinzaparin 4,500 IU once daily). Anti-Xa was measured on day 1 and day 8. Blood samples were taken at 0, 2, 4, 5, 6, 9, 12, 16 and 24 hours. The primary end point was the accumulation factor calculated as a ratio between the maximal anti-Xa activity on day 1and day 8. Fifty-five patients were included (mean age 87.9 ± 5.5 ).The creatinine clearance was 34.7 ± 11.4 ml/min; the body weight was 52.3 ± 8.6 kg. The accumulation factor defined was not significant for tinzaparin (1.05, p=0.29) while it was significantly enhanced for enoxaparin (1.22, p <0.0001). In this pharmacodynamic study performed in elderly patients with impaired renal function, a statistically significant accumulation effect was observed after eight days of prophylactic treatment with enoxaparin but not with tinzaparin, which are two LMWHs with different chain lengths. Trials based on clinical end points should be conducted to evaluate the clinical relevance of these observations.
Keywords: LMWHs; thromboprophylaxis; elderly; renal insufficiency